Determinants of Repayment Performance of Agricultural Loans Clients of RBDI, Abuyog Branch - Loreño, Dustin; Teves, Joviel (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
The study aimed to present the profile of the agricultural loan clients of RBDI, describe the loan assessment process, describe the loan monitoring process in RBDI, identify the determinants of loan repayment performance of RBDI agricultural loan clients and to recommend courses of action to improve loan application assessment, loan monitoring, and loan collection activities of RBDI. The study used the Logit Regression Analysis and the model Y = β0 + β1X1 + β2X2 + β3X3 + β4X4 + . . . . . . . βnXn + e was developed. The binary response is non-payment (default) and payment (non-default). The determinants were the socio-demographic and socio-economic characteristics of the agricultural loan clients, as well as the loan application and monitoring activities of the bank. The profile of the agricultural loan clients of RBDI showed commonalities of the clients in terms of age (63% are above 45 years old), most of them were not able to finish college (53% secondary level) and most are married (77%) with more than 3 dependents (73%). Age was determined as a statistically significant factor affecting the non-payment or loan default. The increase in family size and schooling dependents also raises the probability of default. The result that higher educational level and increase in dependents reduces the probability of default has to be further verified. As the size of land increases and the farming experience increases, the probability of loan default decreases.